Consequences of Maternal Complications in Womens Lives in the First Postpartum Year: A Prospective Cohort Study - Iyengar, Kirti; Yadav, Ranjana; Sen, Swapnaleen (Journal of Health, Population and Nutrition, 2012)
Maternal complications are common during and following childbirth. However, little information is available on the psychological, social and economic consequences of maternal complications on womens lives, especially in a rural setting. A prospective cohort study was conducted in southern Rajasthan, India, among rural women who had a severe or less-severe, or no complication at the time of delivery or in the immediate postpartum period. In total, 1,542 women, representing 93% of all women who delivered in the field area over a 15-month period and were examined in the first week postpartum by nurse-midwives, were followed up to 12 months to record maternal and child survival. Of them, a subset of 430 women was followed up at 6-8 weeks and 12 months to capture data on the physical, psychological, social, or economic consequences. Women with severe maternal complications around the time of delivery and in the immediate postpartum period experienced an increased risk of mortality and morbidity in the first postpartum year: 2.8% of the women with severe complications died within one year compared to none with uncomplicated delivery. Women with severe complications also had higher rates of perinatal mortality [adjusted odds ratio (AOR)=3.98, confidence interval (CI) 1.96-8.1, p=0.000] and mortality of babies aged eight days to 12 months (AOR=3.14, CI 1.4-7.06, p=0.004). Compared to women in the uncomplicated group, women with severe complications were at a higher risk of depression at eight weeks and 12 months with perceived physical symptoms, had a greater difficulty in completing daily household work, and had important financial repercussions. The results suggest that women with severe complications at the time of delivery need to be provided regular follow-up services for their physical and psychological problems till about 12 months after childbirth. They also might benefit from financial support during several months in the postpartum period to prevent severe economic consequences. Further research is needed to identify an effective package of services for women in the first year after delivery. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11318 J HEALTH POPUL NUTR 2012 Jun;30(2):226-240